Passion of St. Crispina - Eugene Rosenblum (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
This publication introduces the fi rst Russian translation of St. Crispina’s Passion. St. Crispina was beheaded in the Roman African city of Theveste on 5th December, 304, during the Great Persecution. The wide popularity of her cult in Roman Africa was attested by St. Augustine. St. Crispina was the last Christian martyr in Africa before the Donatist Schism and was venerated by both Donatists and Orthodox Christians. Various stages of the Passion’s “Donatisation” are represented in various manuscripts. Modern scholars are familiar with three manuscripts containing the Passion of St. Crispina. Two of them were published in the 17th century by Mabillon and Ruinart respectively. Both of these manuscripts perished later. The last manuscript was published in the 20th century by P. Franchi de Cavalieri and was later reprinted in H. Musurillo’s edition of Acta Martyrum. It is regarded as the most authentic MS. The original text of the Passion of St. Crispina was probably composed in the fi rst half of the 4th century. It has no features of the later hagiographic tradition such as the abundance of miracles, detailed description of tortures, etc. On the other hand, it is an elaborate text with its own ideas and style, and does not look like mere court proceedings. The Russian translation being published here is based on Franchi de Cavalieri’s and Musurillo’s edition. The discrepancies between this edition and those of Mabillon and Ruinart are mentioned in the footnotes.